(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND Living donor renal transplantation is widely performed in Switzerland with a superior long-term outcome and lower waiting time compared with deceased renal transplantation. However the chances of receiving a living donor kidney transplant are not the same for all transplant candidates. The current study aimed to identify psychosocial and demographic characteristics that predict lower access to living kidney donation in Switzerland. METHODS The study was a nationwide multicentre study nested within the Swiss Transplant Cohort Study. Pre-transplant demographic, psychosocial and health characteristics of 1126 deceased and 859 living renal transplant recipients were compared using logistic regression analysis. RESULTS Transplant candidates with higher age (odds ratio [OR] per 10 years 0.67, 95% confidence interval [CI] 0.60–0.74), lower education (OR 0.46, 95% CI 0.36–0.59), a work capacity of less than 50% (OR 0.48, 95% CI 0.35–0.66), single or formerly married (OR 0.38, 95% CI 0.26–0.53 / OR 0.37, 95% CI 0.26–0.53) or with a higher hospital depression score (OR per 5 points 0.61, 95% CI 0.50–0.74) were less likely to receive an allograft from a living donor. In some regions of Switzerland candidates were more likely to undergo living transplantation than in other regions. No association was found with gender or income. CONCLUSIONS Interventions to increase access to kidney transplantation from living donors should target transplant candidates of older age, lower education, lower working capacity and not living in a committed relationship. The observed regional differences suggest that additional determinants of living donation may play a role such as population and health professional attitudes toward living donation.